Structures of multidrug and toxic compound extrusion transporters and their mechanistic implications. Issue 2 (3rd March 2016) - Lu, Min
ABSTRACT: Multidrug resistance poses grand challenges to the effective treatment of infectious diseases and cancers. Integral membrane proteins from the multidrug and toxic compound extrusion (MATE) family contribute to multidrug resistance by exporting a wide variety of therapeutic drugs across cell membranes. MATE proteins are conserved from bacteria to humans and can be categorized into the NorM, DinF and eukaryotic subfamilies. MATE transporters hold great appeal as potential therapeutic targets for curbing multidrug resistance, yet their transport mechanism remains elusive. During the past 5 years, X-ray structures of 4 NorM and DinF transporters have been reported and guided biochemical studies to reveal how MATE transporters extrude different drugs. Such advances, although substantial, have yet to be discussed collectively. Herein I review these structures and the unprecedented mechanistic insights that have been garnered from those structure-inspired studies, as well as lay out the outstanding questions that present exciting opportunities for future work.